2009
DOI: 10.1128/aac.00088-09
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor Epoxomicin Has Potent Plasmodium falciparum Gametocytocidal Activity

Abstract: Malaria continues to be a major global health problem, but only a limited arsenal of effective drugs is available. None of the antimalarial compounds commonly used clinically kill mature gametocytes, which is the form of the parasite that is responsible for malaria transmission. The parasite that causes the most virulent human malaria, Plasmodium falciparum, has a 48-h asexual cycle, while complete sexual differentiation takes 10 to 12 days. Once mature, stage V gametocytes circulate in the peripheral blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 28 publications
5
82
0
2
Order By: Relevance
“…Hemoglobin digestion is complete by stage III of gametocytogenesis, as demonstrated by the lack of an effect of cysteine protease inhibitor E64d on food vacuole morphology in stage III to V gametocytes (17,18), and yet the parasite continues to increase in size, suggesting continued metabolism. Additional support for a metabolic shift during sexual development is provided by a report showing that oocyst production, but not asexual growth, is arrested in type II NADH:ubiquinone dehydrogenase and succinate-ubiquinone oxidoreductase knockout parasites (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemoglobin digestion is complete by stage III of gametocytogenesis, as demonstrated by the lack of an effect of cysteine protease inhibitor E64d on food vacuole morphology in stage III to V gametocytes (17,18), and yet the parasite continues to increase in size, suggesting continued metabolism. Additional support for a metabolic shift during sexual development is provided by a report showing that oocyst production, but not asexual growth, is arrested in type II NADH:ubiquinone dehydrogenase and succinate-ubiquinone oxidoreductase knockout parasites (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…dpap2 is transcribed only in gametocytes (16), and its role remains unknown since the gametocyte and mosquito stages were not included in the initial inhibitor analysis (15). Since hemoglobin digestion is essentially complete by stage III of gametocytogenesis (17,18). DPAP2 might have a role in alternative metabolic pathways in late-stage gametocytes and during sporogonic development in the mosquito.…”
mentioning
confidence: 99%
“…Maduramicin-induced rounding is distinct from the response of late-stage gametocytes to the proteasome inhibitor epoxomicin. Following epoxomicin treatment, gametocytes retain their elongated shape but shrink in diameter, ultimately resembling a needle before disintegrating (39). Hliscs et al have recently shown that tubulin and actin remain in complexes in stage V gametocytes (40), but the changes in the cytoskeleton during rounding were not evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, proteasome inhibitors are considered promising antimalarial agents. An essential role of the Plasmodium proteasome has been demonstrated for the liver, blood and gametocyte stages [83,[85][86][87][88][89][90][91]. is often referred to as the parent compound of the thiopeptide antibiotics (for review, see [92]).…”
Section: Antibioticsmentioning
confidence: 99%